International intervention and the problem of legitimacy encounters in postwar Bosnia-Herzegovina - Gilbert, Andrew (Cornell University Press, 2020)
"This book argues for an ethnographic analysis of international intervention as a series of encounters, thereby revealing the open-ended, innovative, and unpredictable nature of international intervention that is usually omitted from the ordered representations of the technocratic vision and the confident assertions of many critiques"--